"We're Very Careful …": The Fertility Desires and Contraceptive Behaviors of Cohabiting Couples. Issue 4 (October 2014) - Sassler, Sharon; Miller, Amanda J.
<x xml:space="preserve">Abstract</x> A growing proportion of nonmarital births are to cohabiting couples, though childbearing is more common among moderately educated cohabitors than among cohabiting college graduates. In this study reasons for social class divergence in fertility behavior are explored. Data are from semistructured interviews with 30 working‐class and 31 middle‐class cohabiting couples. The authors inquired about readiness for parenthood, contraceptive usage, and concurrence about childbearing plans and contraception. Middle‐class couples generally utilized the most effective methods, often relied on two methods, concurred regarding fertility goals, and reported contracepting consistently. Among the moderately educated, contraceptive utilization was lower and reliance on less effective methods greater; they expressed greater ambivalence about preventing conception and discussed contraception less than their middle‐class counterparts. Less educated respondents also mentioned forgetfulness and cost as reasons for sporadic contraceptive use. The study results highlight the need to deepen understanding of how relational processes and couple dynamics contribute to pregnancy avoidance or conception.